PELATIHAN RANUP HIASAN HANTARAN SEBAGAI UPAYA PELESTARIAN BUDAYA ACEH DI GAMPONG BLANG PULO, KECAMATAN MUARA SATU, KOTA LHOKSEUMAWE - Meliza, Richa; Harinawati, Harinawati; Rizki, Aflia; Arifin, Awaludin (Jurnal Solusi Masyarakat (JSM), 2023)
The PKK women's group is the most effective and efficient forum for providing training or in other words providing in-depth knowledge related to cultural preservation, especially Acehnese culture. Culture will be preserved and developed if we continue to hone our abilities in studying and understanding these customs. In fact, the cultural potential of a particular area can survive or experience change depending on the people. So far, some people think that culture can only increase the development of a region, even though if we know and study culture it can develop along with the times without leaving behind the uniqueness of a culture or customs such as the ranup hantaran in Acehnese wedding customs which is one that is mandatory for every person. Acehnese wedding event. Because ranup is a very vital medium in connecting symbolic communication between the two parties or the bride and groom, from the start of an event until the party ends. And most importantly, ranuh is a symbol of glory in glorifying the guests of "Pemulia Jamee" for the people of Aceh. So it is very important for the people of Aceh to preserve the "Ranup Hantaran" culture by developing innovations that are more modern, classic and decorated, which attract more public attention but do not abandon the ranup hantaran culture that has existed from previous ancestors. The aim is an effort to preserve Acehnese culture in the traditional wedding procession of the Acehnese people. Another outcome was that the group of PKK mothers and teenage women were able to innovate and be creative in assembling and designing delivery decorations. The output of the service will result in publication in the OJS journal with ISSN,